2015
DOI: 10.1007/s00429-015-1082-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of connexin36 gap junctions in the human outer retina

Abstract: Retinal connexins (Cx) form gap junctions (GJ) in key circuits that transmit average or synchronize signals. Expression of Cx36, -45, -50 and -57 have been described in many species but there is still a disconcerting paucity of information regarding the Cx makeup of human retinal GJs. We used well-preserved human postmortem samples to characterize Cx36 GJ constituent circuits of the outer plexiform layer (OPL). Based on their location, morphometric characteristics and co-localizations with outer retinal neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 64 publications
3
25
0
1
Order By: Relevance
“…Despite the similarity, subtle differences in the ON sublayer preference of Cx36 plaques and the presence of subpedicle Cx36 aggregations in the OPL was observed. The wealth of subpedicle Cx36 aggregates in the human OPL has been reported previously (Kántor et al, 2016a) and shown that these structures are GJ sites formed by bipolar cell dendrite terminal endings. GJs in subpedicle aggregates connect bipolar cell dendrites that are postsynaptic to the same cone pedicle, thus likely serve a function necessary for photopic visual signaling.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Despite the similarity, subtle differences in the ON sublayer preference of Cx36 plaques and the presence of subpedicle Cx36 aggregations in the OPL was observed. The wealth of subpedicle Cx36 aggregates in the human OPL has been reported previously (Kántor et al, 2016a) and shown that these structures are GJ sites formed by bipolar cell dendrite terminal endings. GJs in subpedicle aggregates connect bipolar cell dendrites that are postsynaptic to the same cone pedicle, thus likely serve a function necessary for photopic visual signaling.…”
Section: Discussionmentioning
confidence: 66%
“…Whereas the human and guinea pig retinas displayed robust Cx36 labels in the outer retina, the rabbit and the squirrel monkey retinas exhibited only sporadic and faint Cx36 puncta. Cx36 plaques in the human and guinea pig retinas were found throughout the OPL and many of them formed strip-like conglomerates that resembled subpedicle Cx36 aggregates found in some species (Feigenspan et al, 2004; O’Brien et al, 2012; Kántor et al, 2016a). Cx36 plaques scattered throughout the inner retina of all four group 2 species, however, their distributions showed some differences as well.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…; Kántor et al. ; Asteriti et al. ), and as elements of electrical synapses, connexins are involved in signal conduction and neuronal excitation control (Maxeiner ).…”
Section: Discussionmentioning
confidence: 99%
“…For OFF-cone bipolar cells, there are a number of studies in a variety of species that strongly suggest the presence of gap junctions, both between the dendrites (Mills 1999;Feigenspan et al 2004;O'Brien et al 2012;Kántor et al 2016) and the axon terminals (Kolb 1979;Jacoby and Marshak 2000;Omi 2015, 2017;Kántor et al 2017) of these cells. In addition, there is evidence that the gap junctions at the dendrites of OFFcone bipolar cells contain Cx36 (Feigenspan et al 2004;O'Brien et al 2012;Kántor et al 2016). Heterologous gap junctions between adjacent ON-cone bipolars have also been reported (Cohen and Sterling 1990;Tsukamoto and Omi 2017).…”
Section: Evidence For Gap Junctions Involving Cone Bipolar Cellsmentioning
confidence: 99%